Efeito do haloperidol sobre o biofilme e sensibilidade antimicrobiana de bacilos gram negativos de infecções relacionadas à saúde - Souza, Paulo Roberto Honório (2023)
Healthcare-related infections caused by Gram-negative bacteria have become a growing problem with the increase of antimicrobial resistance, mainly mediated by biofilm production. For this reason, it is necessary to search for new compounds and drugs that can help in the treatment against these infections. Thus, the present study evaluated the effect of the antipsychotic haloperidol on antimicrobial and antibiofilm sensitivity in Pseudomonas aeruginosa, Acinetobacter baumannii and Klebsiella pneumoniae. Planktonic sensitivity testing to haloperidol alone and in combination with antimicrobials was done by the broth microdilution method to determine the (MIC). The antibiofilm effect was evaluated by quantification of biofilm biomass, stained with crystal violet, and metabolic activity, using resazurin, to determine the minimal biofilm elimination concentration (MBEC). Furthermore, the structure of the biofilm after exposure to haloperiodol was evaluated by confocal microscopy. The minimum inhibitory concentration (MIC) ranges of haloperiodol were 512, 64 to 128 and 128 µg /mL for P. aeruginosa, A. baumannii and K. pneumoniae respectively. In combination, there was a reduction MICs of the antimicrobials in the combination of haloperidol MIC/2 with amikacin. In relation to biofilm, haloperidol caused destructuring of the biomass in all species, in concentrations of 512, 256 and 128 µg /mL the reductions were 73%, 77% and 77% in P. aeruginosa, 78%, 76% and 65% in A. baumannii and 85%, 66% and 51% in K. pneumoniae respectively. The MBECs of the antimicrobials after associating (MBEC/2) were reduced with statistical significance against P. aeruginosa, and the MBEC of meropenem was reduced in all species. In summary, haloperidol inhibits bacterial growth besides dispersing and destructuring the biofilm, and may potentiate the effect of antimicrobials.